Implementation of Counceling in Antenatal Care Services in Puskesmas Genuk of Semarang - Erna Widyastuti; Ngadiyono Ngadiyono (Midwifery and Nursing Research, 2020)
Background: Maternal mortality was one of indicator in the successful development sector. Maternal Mortality rate in Central Java Province in 2016 was 109.65 per 100,000 live births, decreased in 2017 by 88.5 per 100,000 live births (475 cases), and decreased again in 2018 by 78.6 per 100,000 live births (421 cases). At the same time Semarang city also get decreased. There has been a decreased in cases, 23 cases in 2017 to 19 cases in 2018. The aim of this study was to describe antenatal care services in Puskesmas Genuk.Methods: This study was qualitative and quantitative descriptive research. The design of this research was sequential explanatory designs. The population in this study was pregnant woman and Midwife in Puskesmas Genuk Semarang city and were collected by use purposive sampling. The Researcher collect the data use Indepth interview and analyze the result.Results: The Result of this study showed that Midwifery were dominated in middle age (30 year old) and experience more than tenth years (10 years). Midwives knows detail about counseling at ANC services, but have not yet applied the sequences or principles of counseling in carrying out counseling according to the ability of the research subject and according to the needs of the patient. Pregnant mother were classified in diffrents type of risk and they were remember the counceling from Midwife and can answer the question relate to it.Conclusion: All the Midwife were know about giving advice through counceling method, but they still need to use the principal practice in delivering service.